A Brief Look at Jack Kerouac's Syntax - House, Anthony B. (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1988)
Warren Tallman in his article Kerouac's Sound relates Kerouac's style and syntax to the Bop-Era Jazz of the fifties. Tallman analyses an extended sentence from The Subterraneans. He determines that Kerouac's immediate motive is the Bop motive, maximum spontaneity. The narrative melody merges with and is dominated by the improvised details. Also, the novel is written with the driving but hung-up rhythms of a hurrying man who is also, always alas, looking back over his shoulder. The hurrying is in the narrative and the looking back is expressed by shifts from the narrative line which Tallman has identified as musically inspired, and which I have identified as post-posed adjective structures or fillers of what appears to be a French-motivated post-nominal slot in the syntax. I think that there is a syntactic rule in Kerouac's linguistic system which comes from his first language and which accounts for the stylistic effect noted by Tallman. Therefore, the aim of the paper is to examine an extended sentence in Jack Kerouac's The Subterraneans in search of underlying French syntax. Two or more models of analysis will be tried on the corpus in order to resolve the problem or to open it up to further study.